Chemo-enzymatic oxidative cleavage of isosafrole for the synthesis of piperonal. Issue 9 (23rd June 2021) - Tentori, Francesca; Brenna, Elisabetta; Ferrari, Chiara; Gatti, Francesco G.; Ghezzi, Maria Chiara; Parmeggiani, Fabio
Abstract : Piperonal is a key feedstock for the fine chemical industry. A novel process for its production from isosafrole is described, based on lipase-mediated perhydrolysis in flow, followed by batch alkaline treatment and by MnO2 oxidation in flow. Abstract : Piperonal is a key ingredient in the flavour and fragrance industry and a useful intermediate for the synthesis of fine chemicals. It is currently prepared by either ozonolysis or chromic acid oxidation of isosafrole, obtained upon isomerization of naturally abundant safrole. A chemo-enzymatic three-step procedure for the conversion of isosafrole into piperonal is herein described. Lipase-mediated perhydrolysis of EtOAc in the presence of H2 O2 is employed to generate peracetic acid in situ and promote the epoxidation of isosafrole. The reaction mixture is submitted to methanolic KOH treatment to recover the corresponding mixture of vicinal diols. The latter is efficiently oxidized to piperonal using MnO2, periodically regenerated at the expense of tert -butylhydroperoxide (TBHP), which represents the terminal oxidant of this transformation. The use of continuous-flow conditions using a continuously-stirred tank reactor for the epoxidation, and a packed bed reactor for the final oxidation improves the productivity and stability of the whole method, with space–time yields of 75 mmol g −1 h −1 and 120 mmol g −1 h −1, calculated as amount of generated product per amount of catalyst per unit time.